2008
DOI: 10.1038/leu.2008.224
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Tregs express low molecular splice forms of FOXP3 in Sézary syndrome

Abstract: Sé zary syndrome (SS) is an aggressive variant of cutaneous T-cell lymphoma. During disease progression, immunodeficiency develops; however, the underlying molecular and cellular mechanisms are not fully understood. Here, we study the regulatory T cell (Treg) function and the expression of FOXP3 in SS. We demonstrate that malignant T cells in 8 of 15 patients stain positive with an anti-FOXP3 antibody. Western blotting analysis shows expression of two low molecular splice forms of FOXP3, but not of wild-type (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
96
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(101 citation statements)
references
References 47 publications
2
96
0
3
Order By: Relevance
“…As FoxP3 expression is not entirely specific for Treg cells, the definition of ''Treg cells'' has been, at least in part, a functional one. Therefore, the interpretation of data demonstrating that FoxP3 1 CTCL cells suppress conventional T cells is fraught with difficulty, as these cells may suppress conventional T cells in a FoxP3-independent fashion [28]. The finding that the FoxP3 promotor is demethylated in bona fide Treg has shed light on this issue [29].…”
Section: Cell Of Originmentioning
confidence: 99%
See 1 more Smart Citation
“…As FoxP3 expression is not entirely specific for Treg cells, the definition of ''Treg cells'' has been, at least in part, a functional one. Therefore, the interpretation of data demonstrating that FoxP3 1 CTCL cells suppress conventional T cells is fraught with difficulty, as these cells may suppress conventional T cells in a FoxP3-independent fashion [28]. The finding that the FoxP3 promotor is demethylated in bona fide Treg has shed light on this issue [29].…”
Section: Cell Of Originmentioning
confidence: 99%
“…Heid et al recently demonstrated that the malignant T cells in a subset of Sézary patients may be derived from Treg cells, as the malignant clone in these patients not only expressed FoxP3 and suppressed conventional T cells but possessed a demethylated FoxP3 promoter [30]. Whether this subset of patients represents a distinct or overlapping population with the subset of Sézary patients which were recently found to express lowmolecular weight splice forms of FoxP3 is unknown [28]. Therefore, a subset of CTCL patients appears to harbor a Treg-derived clone, although the prognostic and therapeutic implications of this observation remain to be defined.…”
Section: Cell Of Originmentioning
confidence: 99%
“…30 The cells were cultured as previously described. 12,34,35 RNA purification and reverse transcriptase PCR RNA purification and reverse transcriptase PCR (RT-PCR) were performed as described previously, 34 using the primer sets shown in Table S1 (available on the Blood website; see the Supplemental Materials link at the top of the online article). …”
mentioning
confidence: 99%
“…[1][2][3] Previous studies have demonstrated defects in cell-mediated immunity in CTCL patients, including altered cytokine profiles and impaired neutrophil function, which lead to a high incidence of recurrent bacterial and viral infections as a result of decreased Th1-mediated immunity. [4][5][6][7][8][9] It has also been reported that natural killer (NK)-cell function is decreased in CTCL patients, [10][11][12][13][14] which could contribute to an overall decrease in the innate immune response to both neoplastic cells and viral or bacterial pathogens. Previous groups have reported that NK cells from SS patients are capable of responding to activation ex vivo, indicating the potential for development of immune-based therapeutics.…”
Section: Introductionmentioning
confidence: 99%